International Benchmarking on Strategic Management of Health Regulation - Mota, João Paulo; Lima Moreno, Lucas; Vilela, Pedro; Trindade da Silva, Gustavo Henrique (Revista del CLAD Reforma y Democracia, 2025)
The article explores best practices in strategic management across eight health regulatory agencies from various regions — Europe, North America, South America, and Oceania — are explored, with a focus on these institutions’ priorities for protecting and promoting health. Among the common strategic themes identified in the research are innovation, with the use of emerging technologies to improve evaluations and accelerate access to new therapies; environmental sustainability, through the promotion of ecological practices and responsible resource use; international collaboration to confront global threats such as pandemics and antimicrobial resistance; and clear, accessible communication, which is essential for consumers to make informed decisions. Furthermore, it was found that, in a transversal manner, the analyzed institutions are enhancing their risk management systems to anticipate, identify, and mitigate threats — an aspect particularly relevant in the face of health crises and rapid technological evolution. The study delves deeply into the practices of the European Medicines Agency and the Danish Medicines Agency, emphasizing management methodologies, governance structures, and monitoring processes that contribute to effective strategic management. It was also observed that recognition and incentive practices strengthen engagement and ensure sustainable results, offering a comprehensive and relevant perspective for improving health regulation globally.